Solve for x: −2(x + 3) = −2(x + 1) − 4. (1 point)

Other questions on the subject: Mathematics

Mathematics, 21.06.2019, mia12340
Option C is correctStep-by-step explanation:Given: vertex of this parabola is at (-2,-3)To find: coefficient of the squared expression in the parabola’s equation if the x-value is...Read More
2 more answers
Mathematics, 21.06.2019, Monte86
option a is correct.[tex]\frac{\text{original height}}{\text{original base}}=\frac{\text{reduction height}}{\text{reduction base}}[/tex]step-by-step explanation: scale factor: it...Read More
1 more answers
Mathematics, 22.06.2019, cbear5626
simplifying 5(x + -6) = 2(x + 3) reorder the terms: 5(-6 + x) = 2(x + 3) (-6 * 5 + x * 5) = 2(x + 3) (-30 + 5x) = 2(x + 3) reorder the terms: -30 + 5x = 2(3 + x) -30 + 5x = (3 *...Read More
3 more answers
Mathematics, 22.06.2019, shrinu
you forgot the options, but i found them anyways, the correct answer is "john wilson believes that words and actions based on the intellect are superior to those based on emotions"...Read More
1 more answers